Functional MRI for the Assessment of Brain Connectivity in Neurodegenerative Diseases: An Observational Study in Mexico City - Maria Rodriguez; Salazar Torres (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Neurodegenerative diseases are characterized by progressive brain dysfunction and structural changes. Functional MRI (fMRI), a non-invasive imaging technique, offers the potential to assess brain connectivity and identify early biomarkers of these diseases. Methods: This observational study included patients with Alzheimer's disease (AD), Parkinson's disease (PD), and healthy controls in Mexico City. Resting-state fMRI data was acquired, and brain connectivity was analyzed using independent component analysis (ICA) and seed-based correlation analysis (SCA). Results: fMRI revealed altered brain connectivity patterns in AD and PD compared to healthy controls. In AD, decreased connectivity was observed within the default mode network (DMN), while PD patients showed reduced connectivity in the motor network. Conclusion: fMRI provides valuable insights into brain connectivity changes in neurodegenerative diseases. These findings contribute to the development of early diagnostic tools and potential therapeutic targets for AD and PD.